ANALISIS PENGARUH FAKTOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BALI - I GUSTI AYU MADE AGUNG MAS ANDRIANI PRATIWI (Universitas Mahasaraswati K. Mataram, 2024)
Economic growth is often something that many regions desire. This is because good economic growth can improve the welfare of the people in it. Bali Province is one of the provinces in Indonesia that has experienced turbulent economic growth over the last five years, one of the reasons being the Covid-19 pandemic. Moreover, Bali Province has made the tourism sector the main sector supporting the economy in the region. This research is focused on discussing the description of tourism factors on economic growth in Bali Province. The objectives of this research include finding out the influence of the average length of stay, room occupancy rate, and number of tourists partially and simultaneously on economic growth in Bali Province. The approach used in this research is a quantitative approach. This research uses secondary data obtained from BPS Bali Province. The data used in this research is time series data for each Regency/City in Bali Province from 2019-2023. This research uses data processing tools, namely Microsoft Excel and SPSS. The research results show that: 1) the average length of stay has a partially negative and significant effect on economic growth in Bali Province; 2) the room occupancy rate has a partially positive and significant effect on economic growth in Bali Province; 3) the number of tourists has a negative and partially insignificant effect on economic growth in Bali Province; and 4) average length of stay, room occupancy rate, and number of tourists simultaneously have a positive and significant effect on economic growth in Bali Province.